1996
DOI: 10.1103/physrevlett.76.3384
|View full text |Cite
|
Sign up to set email alerts
|

Linear and Nonlinear Optical Characteristics of the Falicov-Kimball Model

Abstract: We calculate the linear and nonlinear optical properties of the Falicov-Kimball model for a mixedvalent system within the self-consistent mean-field approximation. Second-harmonic generation can only occur if the mixed-valent state has a built-in coherence between the itinerant d-electrons and the localized f -holes. By contrast, second-harmonic generation cannot occur for solutions of the model with f -site occupation as a good quantum number. As an experimental test of coherence in mixed-valent compounds we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
125
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(133 citation statements)
references
References 9 publications
4
125
4
Order By: Relevance
“…13 and 14 in contrast to the findings in Ref. 12. Afterwards it has been demonstrated that spontaneous electronic ferroelectricity also exists in the EFKM, provided that the c-and f-bands involved have different parity.…”
contrasting
confidence: 51%
See 2 more Smart Citations
“…13 and 14 in contrast to the findings in Ref. 12. Afterwards it has been demonstrated that spontaneous electronic ferroelectricity also exists in the EFKM, provided that the c-and f-bands involved have different parity.…”
contrasting
confidence: 51%
“…To be a good model of the mixed-valence state, however, one should build in a coherence between c and f particles. 12 This can be achieved by a c-f hybridization term V . Alternatively, a finite f-bandwidth, which is certainly more realistic than entirely localized f-electrons, can also induce c-f coherence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An onsite Coulomb interaction U of both species determines the distribution of the electrons between the f and c sub-systems, and therefore may drive a valence transition, provided there is a way to establish f -c coherence. At first glance this can only be achieved by including a hybridization of the f and c bands 27,28 . It has been shown, however, that a finite f bandwidth, being certainly more realistic than entirely localized f electrons, will also induce f -c transitions 29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, both the Falicov-Kimball model with hybridization 27,28,[32][33][34] and the EFKM [29][30][31]35 have been studied in connection with the exciting idea of electronic ferroelectricity. The origin of electronic ferroelectricity is a spontaneously broken symmetry due to a non-vanishing c † f average, which causes finite electrical polarizability without an external, interbandtransition driving field.…”
Section: Introductionmentioning
confidence: 99%